RANCANG BANGUN MONITORING SUHU DAN KELEMBABAN PADA INKUBATOR PENETASAN TELUR AYAM KAMPUNG BERBASIS IOT - I Made Gede Widi Mahardika; I Wayan Dika; I Kadek Juni Arta (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2025)
In making this final assignment describes in detail the process of designing and building a temperature and humidity monitoring system on an IoT-based chicken egg hatching incubator. Before designing and building the system, a survey was first conducted using the interview method as a basis for benchmarking in designing and building the system. The purpose of this final assignment is to design and realize a temperature and humidity monitoring design system on an IoT-based chicken egg hatching incubator. Temperature and humidity monitoring system to help the IoT-based chicken egg hatching process. The temperature and humidity monitoring system for the chicken egg hatching process has a main component, namely ESP32 as a microcontroller that can be connected to wifi, measuring temperature and humidity values in this system using a DHT22 sensor by comparing using the HTC-2 thermohygrometer calibration tool to get a temperature difference of 0.5 ° C and get a humidity difference of 5% RH, in testing the entire tool using 4 chicken eggs in total. The 4 eggs successfully hatched in the incubator, 3 (75%) were normal eggs, 1 (25%) were defective, and no kampung chicken eggs were identified as dead (0%). Using an incubator can speed up the hatching process of kampung chicken eggs by 20 days